Anti-Gouty Arthritis and Antihyperuricemia Effects of Sunflower (Helianthus annuus) Head Extract in Gouty and Hyperuricemia Animal Models. (27th August 2017) - Li, Lanzhou; Teng, Meiyu; Liu, Yange; Qu, Yidi; Zhang, Yuanzhu; Lin, Feng; Wang, Di
Abstract : This study was performed to investigate the therapeutic effects and possible mechanisms of sunflower (Helianthus annuus) head extract (SHE) on gout. First, the components of sunflower head powder and SHE were analyzed systematically. SHE, especially SHEB (extracted with 20% ethanol and 80% double-distilled water), strongly suppressed the swelling of the ankles in rats with acute gout induced by monosodium urate (MSU) crystals and reduced the levels of uric acid and xanthine oxidase (XO) in mice with hyperuricemia induced by oteracil potassium and yeast extract powder. Hematoxylin and eosin staining indicated that SHEB reduced inflammation cells and increased the joint space in the ankle compared with the control rats with MSU-induced gout. In the rats with acute gout, among 13 detected inflammatory cytokines, SHEB significantly enhanced the serum levels of interleukin-10 and the monocyte chemoattractant protein 1 α . In the mice with hyperuricemia, SHEB reduced the levels of glutathione peroxidase, superoxide dismutase, malondialdehyde, and nitrogen monoxide in liver tissues. The potential therapeutic effects of SHE on gout are probably due to the production of anti-inflammatory cytokines and the suppression of XO activity via the modulation of oxidative stress status.